The Phase Еquilibrium in the HgS–Ga2S3–Bi(Sb)2S3 Systems - Smitiukh, O.V.; Petrus’, I.I. (Physics and Chemistry of Solid State, 2023)
Phase equilibria in the quasi-ternary systems HgS–Ga2S3–Bi(Sb)2S3 were studied by physico-chemical analysis methods on 177 alloys that were synthesized by direct single-temperature method. Phase diagrams of the quasi-binary systems HgS–Bi2S3 and Ga2S3–Bi2S3, six vertical sections (HgGa2S4–HgBi2S4, HgGa2S4–Bi2S3, HgGa6S10–Bi2S3, HgGa6S10–HgBi2S4, HgGa2S4–Sb2S3, and HgS–“GaSbS3”), and liquidus surface projections were investigated. Due to large primary crystallization region of mercury thiogallate, particularly at the HgGa2S4–Bi2S3 and HgGa2S4–HgBi2S4 sections, and low temperature (950-1050 K), the growth of single crystals of mercury thiogallate is possible using solution-melt method.